Neopentecostal fundamentalist thought in Costa Rica - Barrera Rivera, Dan Abner (2024)
This article is a study of neopentecostal fundamentalist thought in Costa Rica within the international context: it exposes what are the main characteristics that make up its identity, in what aspects it resembles pentecostalism and in which it distances itself from it, and what are its differences with the other evangelical christian denomimations. The interest it has in being a protagonist in these first decades of the XXI century in Costa Rican politics is highlighted.